2020
DOI: 10.1097/aog.0000000000003653
|View full text |Cite
|
Sign up to set email alerts
|

Perineorrhaphy Compared With Pelvic Floor Muscle Therapy in Women With Late Consequences of a Poorly Healed Second-Degree Perineal Tear

Abstract: Background and aimsThe life-time risk for a woman to undergo pelvic floor reconstructive surgery due to prolapse or incontinence is 20% and the high risk for recurrence after prolapse surgery is a major challenge. Surgical reconstruction of the perineal body is commonly performed, although studies assessing results of this procedure are scarce. Mid-urethral sling surgery has a cure rate of 80%, but whether the sling endures a subsequent delivery is largely unknown. In this thesis we aimed to investigate whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 196 publications
(224 reference statements)
1
7
0
Order By: Relevance
“…The findings of the present study are consistent with published data on the benefits of reconstructing the perineal body 14,34,36 . Bergman et al showed an improvement in patient satisfaction after perineal reconstructive surgery when compared with physiotherapy 12 . Correspondingly, in this study, the total postoperative scores were greatly reduced, and the item score “Are you experiencing genital discomfort that affects your quality of life?” was significantly decreased, which may be interpreted as high patient satisfaction.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study are consistent with published data on the benefits of reconstructing the perineal body 14,34,36 . Bergman et al showed an improvement in patient satisfaction after perineal reconstructive surgery when compared with physiotherapy 12 . Correspondingly, in this study, the total postoperative scores were greatly reduced, and the item score “Are you experiencing genital discomfort that affects your quality of life?” was significantly decreased, which may be interpreted as high patient satisfaction.…”
Section: Discussionsupporting
confidence: 92%
“…The procedure of perineorrhaphy or perineoplasty is commonly performed concomitant to posterior colporrhaphy 11 . As shown in a randomized control trial by Bergman et al, perineal reconstruction seem to reduce complaints of pelvic floor dysfunction 12 . However, there is a heterogeneity in procedure description and surgical approaches, which are all used interchangeably 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…The training principles were as follows: 10 maximal contractions, each 5 seconds long, 3 times per day, and 1 maximal contraction of 30-60 seconds; continue training for 3 months. 22 No other physical examination was performed by the physiotherapist. The researchers used the smartphone application WeChat to send prewritten messages to participants in the intervention group at 9 am, 2 pm, and 6 pm every day to remind them to perform PFMT.…”
Section: Interventionsmentioning
confidence: 99%
“…Third-and fourth-degree injuries are regarded as ‘high order’ since they are associated with higher risk of urogynaecological, sexual and colon-proctological dysfunctions than in first- and second-degrees [ 4 , 5 ]. Prevalence in developed countries varies, reaching 10.2% in women who had vaginal birth, although there is recognised lack of standardisation in perineal tear identification and is also under-diagnosed on numerous occasions [ 6 , 7 ]. All of these factors added to those that have an impact on women’s health (dyspareunia, chronic pelvic pain, vaginal flatulence, urinary, faecal or anal incontinence, prolapses…) make it difficult to collect data on the economic impact of perineal tears in the in participating health service system [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%